Cohort profile: effect of malaria in early pregnancy on fetal growth in Benin (RECIPAL preconceptional cohort). Issue 1 (8th January 2018) - Accrombessi, Manfred; Yovo, Emmanuel; Cottrell, Gilles; Agbota, Gino; Gartner, Agnès; Martin-Prevel, Yves; Fanou-Fogny, Nadia; Djossinou, Diane; Zeitlin, Jennifer; Tuikue-Ndam, Nicaise; Bodeau-Livinec, Florence; Houzé, Sandrine; et al.
Abstract : Purpose: REtard de Croissance Intra-uterin et PALudisme (RECIPAL) is an original preconceptional cohort designed to assess the consequences of malaria during the first trimester of pregnancy, which is a poorly investigated period in Africa and during which malaria may be detrimental to the fetus. Participants: For this purpose, a total of 1214 women of reproductive age living in Sô-Ava and Akassato districts (south Benin) were followed up monthly from June 2014 to December 2016 until 411 of them became pregnant. A large range of health determinants was collected both before and during pregnancy from the first weeks of gestation to delivery. Five Doppler ultrasound scans were performed for early dating of the pregnancy and longitudinal fetal growth assessment. Findings to date: Pregnant women were identified at a mean of 6.9 weeks of gestation (wg). Preliminary results confirmed the high prevalence of malaria in the first trimester of pregnancy, with more than 25.4% of women presenting at least one microscopic malarial infection during this period. Most infections occurred before six wg. The prevalence of low birth weight, small birth weight for gestational age (according to INTERGROWTH-21st charts) and preterm birth was 9.3%, 18.3% and 12.6%, respectively. Future plans: REtard de Croissance Intra-uterin et PALudisme (RECIPAL) represents at this time a unique resource that will provide information on multiple infectious (including malaria), biological, nutritional and environmental determinants in relation to health outcomes in women of reproductive age, pregnant women and their newborns. It will contribute to better define future recommendations for the prevention of malaria in early pregnancy and maternal malnutrition in Africa. It confirms that it is possible to constitute a preconceptional pregnancy cohort in Africa and provides valuable information for researchers starting cohorts in the future.